2018
DOI: 10.1080/07388551.2018.1496064
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in research and commercialization of exogenous and endogenous RNAi technologies for crops

Abstract: It has only been about 20 years since the first Nobel Prize-winning work on RNA interference (RNAi) in Caenorhabditis elegans was published in the journal Nature. Fast forward to today, and the use of RNA molecules as gene-silencing elements in crops has helped scientists to unveil possible solutions to the global problems of agricultural losses due to pests, viruses, pathogens, and to other abiotic and biotic stresses. The recent proliferation of publications suggests that the technology has gained significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 34 publications
0
49
0
3
Order By: Relevance
“…The analysis of this specific innovation sector reveals that RNAi‐based biocontrol is an emerging technology endowed with a positive patenting trend over time and promising future applications and development . As for the type of applicant involved in this specific innovation cluster, it can be said that globally almost 50% of the total patent activity derives from public R&D, principally from US and Chinese applicants.…”
Section: Commercial Environment For Rna‐based Biocontrol Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of this specific innovation sector reveals that RNAi‐based biocontrol is an emerging technology endowed with a positive patenting trend over time and promising future applications and development . As for the type of applicant involved in this specific innovation cluster, it can be said that globally almost 50% of the total patent activity derives from public R&D, principally from US and Chinese applicants.…”
Section: Commercial Environment For Rna‐based Biocontrol Compoundsmentioning
confidence: 99%
“…The analysis of this specific innovation sector reveals that RNAi-based biocontrol is an emerging technology endowed with a positive patenting trend over time and promising future applications and development. 25 As for the type of applicant involved in this specific innovation cluster, it can be said that globally almost 50% of the total patent activity derives from public R&D, principally from US and Chinese applicants. As for the private sector, Agriculture biotechnology (agbiotech) companies are still the major players in patent production, but the sector is characterized by a greater concentration in the early years of development, while recently a larger number of small to medium-sized players have become involved in this research area.…”
Section: Commercial Environment For Rna-based Biocontrol Compoundsmentioning
confidence: 99%
“…RNAi has been used for over 20 years to evaluate gene function in insects [ 43 , 44 , 45 , 46 ], but only recently has its utility in more commercial applications, including pest management, been considered [ 47 , 48 , 49 , 50 , 51 ]. Early studies on coleopteran and lepidopteran pests first demonstrated the potential of RNAi to induce lethality through the knockdown of critical functional genes [ 36 , 37 ].…”
Section: Rnai As a Pest Management Strategy: Need For Greater Specmentioning
confidence: 99%
“…Beginning with studies that proved that artificial double-stranded RNAs cause RNA interference [9], the efficiency of this strategy for the protection of plants from pathogenic organisms and viruses has been convincingly proved [27,28]. In this review, we describe examples of potential practical application of RNA interference in the protection of plants from pathogens.…”
Section: Introductionmentioning
confidence: 99%